Cuckoo Search Based DTC of PMSM - Amir Yassin; Said Wahsh; M. Badr (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Hysteresis controllers (HC) are used to limit the torque and flux in the control band in conventional configuration of direct torque control (DTC) while in the space vector pulse width modulated (SVPWM) DTC, the HC are switched to PI or PID controllers. This paper presents a modern approach for the speed control applied on a DTC of a permanent magnet synchronous motor (PMSM) using the Cuckoo Search Optimization (CSO) algorithm in order to optimize the PI speed controller parameters of the outer loop and PID flux and torque controllers of the inner loop. The system is tested at no load and with a step change in load.The performance of the controllers is presented and the results of simulation indicate a very rapid dynamic response and the system achieves the steady state (SS.) in a very short time. Also it shows that both the SS. and dynamic performances are improved by applying of the CSO algorithm. The proposed DTC simulation model of the PMSM is presented using MATLAB / SIMULINK and capable of simulating both the steady-state and dynamic response. The CSO results are compared with another control strategy that incorporates fuzzy logic controller (FLC) with DTC.